Innovative technologies and learning : first International Conference, ICITL 2018, Portoroz, Slovenia, August 27-30, 2018, Proceedings /: first International Conference, ICITL 2018, Portoroz, Slovenia, August 27-30, 2018, Proceedings. (2018) - Unknown
No abstract available